PENGEMBANGAN EKONOMI KREATIF DAN KOLABORASI PENDIDIKAN, SAINS, SERTA TEKNOLOGI UNTUK MENINGKATKAN PENDAPATAN, DAYA SAING, DAN KESEJAHTERAAN KELUARGA DI DESA BATANG KUIS, KABUPATEN DELI SERDANG - Diana Suita; Liza Fitriana; Haida Dafitri; Kalvin Chiuloto; Johan Oberlyn Simanjuntak; Simon Petrus Simorangkir (MAJU : Indonesian Journal of Community Empowerment, 2026)
The community service initiative in Batang Kuis Village aims to empower the community through the development of the creative economy—leveraging collaboration across education, science, and technology—to sustainably enhance family income, competitiveness, and well-being. The program involves training in entrepreneurial skills and digital technology utilization, alongside efforts to harness local potential, enabling the community to develop creative products with added value and access to broader markets. A participatory approach is employed, engaging business owners, community leaders, and academics to optimize program outcomes. Key challenges identified include limited access to technology, a lack of knowledge regarding digital marketing, and insufficient collaboration among stakeholders. Analysis indicates that capacity building through education and mentoring will create new business opportunities and boost the competitiveness of local products. The expected impact includes increased family income, job creation, and improved community welfare. Implemented solutions encompass continuous training, the development of digital marketing platforms, facilitation of access to micro-capital, and the establishment of robust collaborative networks among various parties. Ultimately, this initiative seeks to foster comprehensive and self-reliant economic growth within the village.